2023
DOI: 10.1186/s12916-023-02742-9
|View full text |Cite
|
Sign up to set email alerts
|

Maternal prenatal cholesterol levels predict offspring weight trajectories during childhood in the Norwegian Mother, Father and Child Cohort Study

Abstract: Background Numerous intrauterine factors may affect the offspring’s growth during childhood. We aimed to explore if maternal and paternal prenatal lipid, apolipoprotein (apo)B and apoA1 levels are associated with offspring weight, length, and body mass index from 6 weeks to eight years of age. This has previously been studied to a limited extent. Methods This parental negative control study is based on the Norwegian Mother, Father and Child Cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Additionally, we compared each type of embryo transfer to OI/IUI. We identified the following potential confounders from the literature: parental causes of infertility [34], maternal and paternal age at conception (restricted cubic splines with 3 knots) [35], maternal and paternal highest educational level at conception [36], maternal country of origin [37], maternal BMI (restricted cubic splines with 3 knots) [38], maternal smoking status [39], maternal and paternal hyperlipidemia or use of lipid-modifying drugs [40], maternal and paternal hypertension or use of antihypertensive drugs [41], presence/absence of diabetes (I or II) [42], parity [43], and year of conception [44]. To adjust for confounding, we used stabilized inverse probability of treatment weighting (IPTW) including the following steps [45]: For each child and each comparison, we used the listed potential confounders to compute a propensity score (i.e., the predicted probability of being exposed) using a logistic regression model and then graphically displayed the distribution of propensity scores across the various exposure and comparison cohorts (S1 Fig) . We then used the propensity score to reweight the population by stabilized IPTW and truncated the extreme weights (the 1st and 99th percentiles) [45].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we compared each type of embryo transfer to OI/IUI. We identified the following potential confounders from the literature: parental causes of infertility [34], maternal and paternal age at conception (restricted cubic splines with 3 knots) [35], maternal and paternal highest educational level at conception [36], maternal country of origin [37], maternal BMI (restricted cubic splines with 3 knots) [38], maternal smoking status [39], maternal and paternal hyperlipidemia or use of lipid-modifying drugs [40], maternal and paternal hypertension or use of antihypertensive drugs [41], presence/absence of diabetes (I or II) [42], parity [43], and year of conception [44]. To adjust for confounding, we used stabilized inverse probability of treatment weighting (IPTW) including the following steps [45]: For each child and each comparison, we used the listed potential confounders to compute a propensity score (i.e., the predicted probability of being exposed) using a logistic regression model and then graphically displayed the distribution of propensity scores across the various exposure and comparison cohorts (S1 Fig) . We then used the propensity score to reweight the population by stabilized IPTW and truncated the extreme weights (the 1st and 99th percentiles) [45].…”
Section: Discussionmentioning
confidence: 99%
“…Apo A and Apo B play important roles in lipid metabolism, cholesterol transport, absorption, and metabolism. Several studies have shown the relationship between Apo A and Apo B levels during pregnancy and pregnancy outcomes 30. 32 Smedts et al and Cao L et al both found that maternal Apo B levels in early pregnancy were the best predictor of CHD in offspring, but this relationship weakened after adjusting for confounding factors in Cao L et al's study.…”
mentioning
confidence: 93%
“…Data from the Norwegian Mother, Father and Child Cohort Study showed that maternal pre-natal cholesterol levels also predicted offspring weight trajectories during childhood. 15 …”
mentioning
confidence: 99%